Potensi Daun Katuk (Sauropus Androgynus) Sebagai Sayuran Superfood - Sri Mulyati; Nurhidayat, Agus Irpan; Fatika Faturrochman, Fedora Firda; Dzaqiah, Meila Nazwa; Rendra RS, Esta (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Sweet Leaf Bush (Sauropus androgynus), a plant native to Southeast Asia, have long been recognized as a food and traditional medicine rich in health benefits. Its nutritional content, which includes protein, fiber, vitamins A, C, and K, as well as minerals such as calcium and iron, makes it a potential superfood. In addition, bioactive compounds such as saponins, flavonoids, and tannins in sweet leaf bush have antibacterial, anticancer, and immune system boosting properties. The health benefits of sweet leaf bush are especially evident in breastfeeding mothers due to its ability to increase breast milk production. With its various nutritional contents, sweet leaf bush have great potential to be developed into innovative and practical food products. This study uses secondary data from scientific journals and other publications to explore the potential of sweet leaf bush as a superfood that can increase the diversity of healthy food products in Indonesia. This study shows that the utilization and dissemination of information related to the potential of sweet leaf bush as a superfood can support local food security and strengthen people's healthy diets.